Assessment of the Factors Militating Against Girl-Child Education in Kontagora Local Government Area, Niger State - Ahmed, Aliyu Tanko; Gyong, Yerima Emmanuel (Kashere Journal of Politics and International Relations, 2024)
The study evaluated factors that constrain and hinder Girl-child education in Kontagora Local Government Area of Niger State, Nigeria. Primary data was used for this study. The theoretical framework used for this study is a synthesis of Erikson’s psychosocial theory. The descriptive statistic and percentages were used to examine factors that militate against Girl-child education in Kontagora Local GovernmentArea of Niger State. The chi-square test was also used to test hypothesis by evaluating the association between the factors that militate and hinder Girl-child education at secondary school level. It was found that traditional practices in study area do not permit the education of the Girl-child. However, poverty and parental ignorance played a vital role in preventing Girl-child education in Kontagora Local Government Area. Although poor parental education and awareness is a hindrance to girl-child education in study area, it established that there is a significant association between the factors militating against the Girl-children in general and Girl-child education at secondary level in Kontagora Local Government Area of Niger State. It was recommended that there is need for the government to introduce cultural and heritage policies in the education system. These can serve as catalysts to ignite Girl-child development in the study area. A policy of scholarships and free education could also be introduced to encourage and boost the morale of parents. This could transform their attitudes leading to positive outcomes that can lead to development of Girl-child education.